The Effect of Antenna Movement and Material Properties on Electromagnetically Induced Transparency in a Two-Dimensional Metamaterials - Mojtaba Servatkhah; Hadi Alaei (Journal of Optoelectronical Nanostructures, 2016)
Increasing development of nano-technology in optics and photonics by using modern methods of light control in waveguide devices and requiring miniaturization and electromagnetic devices such as antennas, transmission and storage as well as improvement in the electromagnetic tool, have led researchers to use the phenomenon of electromagnetically induced transparency (EIT) and similar phenomena in metamaterials. In this work, we introduce a metamaterial structure in nanometer dimensions and THz frequency region. Moreover, by broking the geometrical symmetry structure, we offer EIT with high transmittance and more Q-factor in comparison, to our knowledge, with previous studies of two-dimensional structure, in the infrared region. These achievements can be a good choice for slow light applications and can be used to amplify light in nanostructure and also to detect the infrared light. Finally, we study the effect of changing the metal on the proposed metamaterial. Moreover, in this study, numerical calculations and simulations are done by FDTD methodphenomenon of electromagnetically induced transparency (EIT) and similar phenomena in metamaterials. In this work, we introduce a metamaterial structure in nanometer dimensions and THz frequency region. Moreover, by broking the geometrical symmetry structure, we offer EIT with high transmittance and more Q-factor in comparison, to our knowledge, with previous studies of two-dimensional structure, in the infrared region. These achievements can be a good choice for slow light applications and can be used to amplify light in nanostructure and also to detect the infrared light. Finally, we study the effect of changing the metal on the proposed metamaterial. Moreover, in this study, numerical calculations and simulations are done by FDTD method.